Engaging the Community: Building Effective Partnerships in Sexual Violence Prevention. (September 2018) - Levine, Ethan Czuy
Sexual violence is a multifaceted problem with individual, interpersonal, institutional, and cultural dimensions. Researchers have increasingly turned to social institutions, such as nonprofit agencies, in their efforts to understand and ultimately prevent aggression and victimization. Drawing on interviews with 30 scientists and other scholars, this study explored sexual violence researchers' experiences with and approaches to collaborating with local communities and institutions. Participants shared diverse experiences working with institutionalized and noninstitutionalized local communities, antiviolence advocates and social workers, medical providers, police, attorneys, employees of bars and restaurants, educators, and university administrators. Many noted that the commitments that motivate researchers may be insufficient for engaging community partners. The aim of ending violence, in itself, may not be enough. Narratives of trauma, of risk and safety, may not be enough. Concerns about limited resources and potential backlash or liability may dissuade community members and institutions from partnering with researchers in prevention. Distrust may also pose a barrier. Fortunately, researchers have developed promising strategies for engaging institutional partners despite these concerns. These include cultivating mutual partnerships, in which researchers prioritize institutional input and commit to giving back to their partners and surrounding communities; combining awareness and prevention, in which efforts to raise awareness through institutions are coupled with the development of concrete action plans; and reframing the problem, in which sexual violence or its outcomes are connected with established institutional priorities.